Monogenic diabetes in New Zealand - An audit based revision of the monogenic diabetes genetic testing pathway in New Zealand - Harrington, Francesca; Greenslade, Mark; Colclough, Kevin; Paul, Ryan; Jefferies, Craig; Murphy, Rinki (Frontiers in Endocrinology, 2023)
Aims: To evaluate (a) the diagnostic yield of genetic testing for monogenic diabetes when using single gene and gene panel-based testing approaches in the New Zealand (NZ) population, (b) whether the MODY pre-test probability calculator can be used to guide referrals for testing in NZ, (c) the number of referrals for testing for Māori/Pacific ethnicities compared to NZ European, and (d) the volume of proband vs cascade tests being requested. Methods: A retrospective audit of 495 referrals, from NZ, for testing of monogenic diabetes genes was performed. Referrals sent to LabPlus (Auckland) laboratory for single gene testing or small multi-gene panel testing, or to the Exeter Genomics Laboratory, UK, for a large gene panel, received from January 2014 – December 2021 were included. Detection rates of single gene, small multi-gene and large gene panels, and cascade testing were analysed. Pre-test probability was calculated using the Exeter MODY probability calculator and ethnicity data was also collected. Results: The diagnostic detection rate was widely variable across genes, from 32% in GCK, to 2% in HNF4A, with single gene or small gene panel testing averaging an 12% detection rate . Small multi-gene panel testing gave only an 9% detection rate. However, using a large gene panel, this improved to 22%. The neonatal panel had a 40% detection rate . 45% (67/147) of patients aged 1-35 years at time of diagnosis scored <20% on MODY pre-test probability, of which 3 had class 4/5 variants in HNF1A, HNF4A or HNF1B. Ethnicity data correlated with population ethnicity for Māori (15.3%), but Pacific People appear under-represented (8.4%). Only 1 in 6 probands generated a cascade test. Conclusions: A new monogenic diabetes testing algorithm for NZ is proposed, which directs clinicians to choose a large gene-panel in patients without syndromic features who score a pre-test MODY probability of above 20%.